Vaping-Induced Lung Injury: A Case of Lipoid Pneumonia Associated with E-Cigarettes Containing Cannabis - Bryno Gay; Zachary Field; Sachin Patel; Rodrigo Murillo Alvarez; Wael Nasser; Mario Madruga; S. J. Carlan (Case Reports in Pulmonology)
Electronic cigarette, or vaping product use-associated lung injury (EVALI), is a group of lung disorders associated with vaping and e-cigarette products that has previously been categorized as a diagnosis of exclusion and best described as an exogenous lipoid pneumonia or chemical pneumonitis. Here, we describe the onset of an exogenous cause of lipoid pneumonia in an otherwise healthy patient using cannabis-containing electronic cigarettes. We explore similarities in the clinical case, define a common clinical presentation with progression of disease, characteristic radiographic findings along with pathological diagnosis and management.